Absorption and emission spectroscopic parameters of Nd3+ and Eu3+ ions in their hexamethylphosphoramide complexes - Ribeiro, Sidney José Lima [UNESP]; Massabni, A. M. G. [UNESP]; Stucchi, Elizabeth Berwerth [UNESP] (Elsevier, 1991)
Syntheses of the following complexes are reported: LnX3·6L, LnX′3·4L, LnX″3·3L and Eu(NCS)3·3L, where Ln = Nd3+, Eu3+; L = hexamethylphosphoramide (hmpa); X = ClO4 -, PF6 -; X′ = NCS-, NO3 -, Br-, ClO4 -; X″=Cl-. Spectra of the complexes of Nd3+ (absorption) and Eu3+ (emission) in dichloromethane solutions were measured. The oscillator strengths of the Nd3+ f-f absorption bands within the 11 000-30 000 cm-1 region were determined and the τλ intensity parameters were obtained according to the Judd-Ofelt formalism. Covalency parameters were also determined for the Nd3+ complexes. The intensities relationship η21 of the 5D0→7F2 and 5D0→7F1 transitions of the Eu3+ was calculated. A good correlation between τ2 and the oscillator strength of the hypersensitive band of Nd3+ was found, as well as a correlation between τ2 and η21. There are only qualitative relations between τ2 and the covalency parameter. © 1991.